2017
DOI: 10.1021/acs.jctc.6b01130
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Organic Molecules to van der Waals Materials: Comparison of Fluorographene and Fluorographite with Graphene and Graphite

Abstract: Understanding strength and nature of noncovalent binding to surfaces imposes significant challenge both for computations and experiments. We explored the adsorption of five small nonpolar organic molecules (acetone, acetonitrile, dichloromethane, ethanol, ethyl acetate) to fluorographene and fluorographite using inverse gas chromatography and theoretical calculations, providing new insights into the strength and nature of adsorption of small organic molecules on these surfaces. The measured adsorption enthalpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 70 publications
4
37
0
Order By: Relevance
“…1 ). 17 , 19 , 20 The surface energies measured at low coverage are a result of the intermixing of adsorption on high-energy sites and basal plane adsorption. 17 The amount of high-energy sites is rather low, which is indicated by only a slightly concave shape of the surface energy, particularly in comparison with analogical iGC measurements on graphite.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). 17 , 19 , 20 The surface energies measured at low coverage are a result of the intermixing of adsorption on high-energy sites and basal plane adsorption. 17 The amount of high-energy sites is rather low, which is indicated by only a slightly concave shape of the surface energy, particularly in comparison with analogical iGC measurements on graphite.…”
Section: Resultsmentioning
confidence: 99%
“…The aromatic surface of graphene [19,20] makes it an ideal substrate for immobilization of these organic nanorings through CH• • • π and π • • • π noncovalent interactions. Graphene nano-sized flakes (or nanoislands on other substrates) are extremely useful models to study these highly local interactions in adsorption processes [21][22][23], as they can also be easily functionalized [24] and produced by STM experiments through mechanical contact between the tip and the surface or through electro-exfoliation [25]. Once a reasonable nano-sized graphene flake is selected one can choose the corresponding nanoring size to avoid pronounced edge effects.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the surface properties of FG, recent studies by inverse gas chromatography revealed that GrF has a lower surface energy (of ∼80 mJ m −2 ) than graphite [35] . Additionally, the adsorption enthalpies of organic molecules are similar or even slightly lower to FG than to graphene [101] , [102] .…”
Section: Propertiesmentioning
confidence: 94%